Correlação entre a intenção de uso e uso das tecnologias de método de pagamento on-line Pix e MB WAY - Neves, Ramilo de Moraes Coutinho (2021)
E-commerce is the fastest growing type of commerce in recent years, and this growth is accompanied by new online payment method technologies that allow consumers more convenience when making payments, including using their mobile devices. The payment method technologies used in this study are: Pix, which was created by the Central Bank of Brazil, and MB WAY, which was created by SIBS - Forward Partner in Payments. Both technologies feature the reading of a QR Code or the inclusion of keys to make and approve payments quickly and securely. This study aims to verify the correlation between the intention to use and use Pix, by Brazilian consumers, and MB WAY, by Portuguese consumers, based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). Empirical research with a quantitative approach was carried out through the application of a questionnaire, available on the internet using the google forms tool. The results of this study allow us to conclude that there is a correlation between the intention of use and use based on the constructs performance expectation, effort expectation, facilitating conditions, hedonic motivation, price value and habit for Portuguese consumers and the only one that could not be proven for this universe it was the social influence, and for Brazilian consumers, there is a correlation between the intended use and use based on all constructs.